Addressing disease-related malnutrition in healthcare: A Latin American perspective (2016)
Alarmingly high rates of disease-related malnutrition have persisted in hospitals of both emerging and industrialized nations over the past 2 decades, despite marked advances in medical care over this same interval. In Latin American hospitals, the numbers are particularly striking; disease-related malnutrition has been reported in nearly 50% of adult patients in Argentina, Brazil, Chile, Costa Rica, Cuba, Dominican Republic, Ecuador, Mexico, Panama, Paraguay, Peru, Puerto Rico, Venezuela, and Uruguay. The tolls of disease-related malnutrition are high in both human and financial terms - increased infectious complications, higher incidence of pressure ulcers, longer hospital stays, more frequent readmissions, greater costs of care, and increased risk of death. In an effort to draw attention to malnutrition in Latin American healthcare, a feedM.E. Latin American Study Group was formed to extend the reach and support the educational efforts of the feedM.E. Global Study Group. In this article, the feedM.E. Latin American Study Group shows that malnutrition incurs excessive costs to the healthcare systems, and the study group also presents evidence of how appropriate nutrition care can improve patients' clinical outcomes and lower healthcare costs. To achieve the benefits of nutrition for health throughout Latin America, the article presents feedM.E.'s simple and effective Nutrition Care Pathway in English and Spanish as a way to facilitate its use. © 2014 The American Society for Parenteral and Enteral Nutrition.